Point-of-Care Ultrasound for Central Venous Assessment in the Emergency Department: A Prospective Study Comparing the Femoral and Internal Jugular Veins. Issue 1 (16th October 2020) - Pandya, Lori; Cooper, Michael; Patel, Nishit; Leonard, David; Fernandes, Neil; Spear, Dave; Nesiama, Jo-Ann
Abstract : Objectives: The objective of this study was to estimate the width, height, and depth of the femoral vein (FV) and internal jugular vein (IJV), both sites of potential central line placement in children, using point-of-care ultrasound. Methods: This was a prospective observational study. Point-of-care ultrasound was used to measure the width, height, and depth of the right FV and IJV in 100 children. The primary outcome was a comparison of the widths of the FV and the IJV in the same child. Our primary hypothesis was that the IJV would be wider than the FV. Secondary outcome measures included comparison of the heights and depths the FV and IJV and description of vessel overlap frequency between the 2 sites. Results: A total of 106 children were enrolled, with 6 subjects excluded, and equally divided into 5 age groups (0–30 days, 1–24 months, 2–5 years, 6–11 years, and 12–17 years). The FV/IJV width ratios (95% confidence interval) by age were 0.58 (0.49–0.68), 0.53 (0.43–0.66), 0.57 (0.49–0.67), 0.68 (0.55–0.85), and 0.73 (0.62–0.85), all P < 0.002. The FV/IJV height ratios were <1 in all age groups, with P < 0.003 in the 4 youngest age groups. The FV/IJV depth ratios were >1 in 6 to 11 years ( P = 0.018) and 12 to 17 years ( P < 0.001). Conclusions: The IJV was significantly wider and taller than the FV in the same child in all age groups. The FV was significantly deeper than the IJV in children 6 years and older. This supports the use of the IJV as a potential site when placing ultrasound-guided central lines in children.